Topical Allium cepa Ethanol Extract Restores SOD and VEGF Without Increasing Hair Length in UV-B-Exposed Wistar Rats - Ajeng Hana Anjani Djajaatmadja; I Made Winarsa Ruma; Ida Ayu Dewi Wiryanthini; Agung Nova Mahendra; Bagus Komang Satriyasa; I Wayan Sugiritama (HM Publisher, 2026)
Background: Ultraviolet B (UV-B) accelerates hair photoaging by depleting cutaneous superoxide dismutase (SOD) and dysregulating vascular endothelial growth factor (VEGF). Red onion (Allium cepa) is rich in flavonoids and organosulfur precursors of hydrogen sulphide that may enhance both antioxidant defenses and pro-angiogenic signaling. This study evaluated topical Allium cepa ethanol extract on cutaneous SOD, VEGF, and hair length in UV-B-exposed Wistar rats. Methods: Twenty male Wistar rats (3–4 months, 180–200 g) were randomly allocated to five groups (n=4): normal control without UV-B (KN), placebo with UV-B and base preparation (K-), and three groups receiving topical Allium cepa ethanol extract at 1% (P1), 2% (P2), and 4% (P3). UV-B was administered at 65 mJ/cm² thrice weekly for 21 days. SOD and VEGF were measured by ELISA; hair length by digital calipers. Data were analyzed by one-way ANOVA with Tukey post-hoc tests. Results: UV-B reduced SOD by 77.2% and VEGF by 61.7% versus normal. Topical Allium cepa restored both dose-dependently: SOD reached 13.85±0.27 U/mL and VEGF reached 43.00±1.13 ng/L at 4%, with 4% VEGF exceeding normal by 33% (p<0.001). The 2% concentration restored VEGF to physiological levels (p=0.493). Hair length did not differ across groups (p=0.394). The cross-group SOD–VEGF correlation was strongly positive (Pearson r=0.804). Conclusion: Topical Allium cepa ethanol extract is a potent dose-dependent enhancer of cutaneous SOD and VEGF in UV-B-exposed rats. The dissociation between robust biochemical recovery and the unchanged hair-length endpoint supports Allium cepa as an antioxidant and pro-angiogenic adjunct for hair photoaging warranting extended-duration translational studies.